Optoelectronic properties of transition metals doped cubic Cadmium Sulfide. (August 2015) - Benstaali, W.; Bentata, S.; Abbad, A.; Bentounes, H.A.; Lantri, T.
Abstract: First principle calculations have been performed to obtain detailed electronic structure, and optical properties of Fe, Pd and Mn doped CdS. The results show that FeCdS and PdCdS show spin polarization phenomenon since they have a metallic behavior for spin down and an insulating character for spin up. This half-metallic character makes these compounds potential candidates for applications in spintronics. Moreover, optical properties show the appearance of pronounced peak in PdCdS and FeCdS at low energies. Consequently, these peaks prove that there is a strong energy absorption which offers the possibility of using these doped compounds for specific applications.